The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1242/jeb.167254
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of body fatness: trading off disease and predation risk

Abstract: Human obesity has a large genetic component, yet has many serious negative consequences. How this state of affairs has evolved has generated wide debate. The thrifty gene hypothesis was the first attempt to explain obesity as a consequence of adaptive responses to an ancient environment that in modern society become disadvantageous. The idea is that genes (or more precisely, alleles) predisposing to obesity may have been selected for by repeated exposure to famines. However, this idea has many flaws: for insta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
88
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(89 citation statements)
references
References 327 publications
(311 reference statements)
1
88
0
Order By: Relevance
“…The body fat hypothesis has been proposed to explain sex differences in life expectancy . Stored body fat serves as the major energy reserves during negative energy balance . Sexual dimorphism in human body composition is widely recognized, with adult men having higher skeletal muscle mass and lower fat mass than women .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The body fat hypothesis has been proposed to explain sex differences in life expectancy . Stored body fat serves as the major energy reserves during negative energy balance . Sexual dimorphism in human body composition is widely recognized, with adult men having higher skeletal muscle mass and lower fat mass than women .…”
Section: Discussionmentioning
confidence: 99%
“…Stored body fat serves as the major energy reserves during negative energy balance . Sexual dimorphism in human body composition is widely recognized, with adult men having higher skeletal muscle mass and lower fat mass than women . Therefore, women are expected to carry higher energy reserves.…”
Section: Discussionmentioning
confidence: 99%
“…Solid evidence supports that low circulating leptin acts as a strong starvation signal by potentiating appetite and protecting against a dangerous degree of thinness [7,32,33]. Consequently, leptin is considered an important mediator of the lower intervention point [31] (Fig 2). Although research into this aspect of body weight regulation has revealed one explanation why it is so difficult to maintain a large weight loss [3], it provides no clue as to why some individuals become obese in the first place.…”
Section: Between Biological Boundaries: How Do Mammals Maintain a Stamentioning
confidence: 92%
“…Because physiological regulators are less active within this zone, fat mass can fluctuate freely until it "bounces into" either the upper or lower boundary. When this happens, powerful biological feedback forces are engaged to ensure that adipose depot size does not change to an extent that jeopardizes the ability to escape from lifethreating dangers or to survive periods of starvation and sickness-induced anorexia [31]. Solid evidence supports that low circulating leptin acts as a strong starvation signal by potentiating appetite and protecting against a dangerous degree of thinness [7,32,33].…”
Section: Between Biological Boundaries: How Do Mammals Maintain a Stamentioning
confidence: 99%
See 1 more Smart Citation